Uterine rupture of uterus bicornis at 19 weeks of gestation organ preservation by performing a hemihysterectomy. Issue 6 (2016) - Binder, Simon; Lux, Jörg; Bizjak, Gabriele; Fehm, Tanja; Hepp, Philip
No abstract available